The - Balisacan, Arsenio M. (Oxford University Press, 2003)
This book examines all major facets of the Philippine economy and development policy. Contributors to this volume look both to the past and to the future, and their approaches are variously descriptive, analytical, interpretive, and comparative. The book assesses trends since the 1980s, identifies major policy issues, and provides a balance sheet of achievements and deficiencies over the past decade and beyond. It highlights future challenges that need to be addressed if the country is to embark on a sustainable, durable, and equitable growth trajectory...